The Application of PjBL with STEM Integration: Its Effect on Science Problem-Solving Abilities - Subekti, Ananda Oktaviani; Rahayu, Rina; Trisnowati, Eli (Jurnal Inovasi Pendidikan IPA, 2025)
This study aims to investigate the effectiveness of the PjBL Model with the STEM Approach in improving junior high school students' science problem-solving abilities. It is a quasi-experiment with a nonequivalent control group design. The population is grade VIII students of State Junior High School 3 Magelang, and the sample is grade VIIIB and VIIIF students, established by using the purposive sampling technique, with VIII B students as the experimental class and VIIIF students as the control class. The data were collected using a test. The results showed the post-test scores of the experimental class were higher than those of the control class with the sig. (2-tailed) < 0.05, namely 0.000 from the independent sample t-test. The N-gain test shows that the N-gain of the experimental class is higher than that of the control class (0.678> 0.412), both in moderate criteria, so it can be concluded that the PjBL Model with the STEM Approach can improve the science problem-solving abilities of junior high school students.